The Analysis of Different Perceptions between PPAk Students, KAP Auditors and Company Manager toward Public Accountant Responsibility Related to Expectation Gap - Gen Norman Thomas (Bina Nusantara University, 2015)
This study is in research domain of behavioral accounting that is based on the current aspect is still interesting to explore.This study aims to reveal differences in perceptions of students, auditors and company managers to public accountant responsility related to expectation gap that includes fraud disclosures, maintain of independence, providing early warning of possibility of business failure, violation of law and improving audit quality. This research is quantitative research using descriptive and comparative research method. Data collective tehnique use survey method with sample was determined by non probability under convenience sample. Data quality was examined with using cronbach’s alpha shows the data is valid and realible. Data normality test used independent t test showed data in normal curve, no multicolinearity and no hetrogenity. First to fifth hyphotesis showed the difference of perception amongs PPAk students, KAP’s auditors and company managers to public accountant responsibility in various dimensions of expectation gap in Jakarta.